(untitled) (Studia Prawnicze / The Legal Studies, 1993)
Przepisy statutowe adresowane są do każdego, kto znajdzie się w sytuacji przewidzianej przez normę prawną statutu. Chodzi tu m.in. o normy ustalające zasady korzystania z gminnych (osiedlowych, dzielnicowych) obiektów i urządzeń użyteczności publicznej, biblioteki gminnej, ośrodka zdrowia lub teatru (art. 40 ust. 2 pkt 4), a także zasady tworzenia jednostek pomocniczych - sołectw, osiedli, dzielnic miejskich (art. 5). W tym kontekście nie wydaje się uzasadniona teza, że statuty gminne (miejskie, dzielnicowe, m. st. Warszawy) nie mogą stanowić podstawy prawnej nakładania obowiązków na obywateli i ich organizacje ani podstawy udzielania im upoważnień. Budżet gminy oraz program gospodarczy tej wspólnoty samorządowej są rodzajami miejscowych przepisów powszechnie obowiązujących. Statutory provisions are intended for anyone who is in the situation envisaged by the legal standard of the statute. These include, inter alia, the standards setting out the rules for the use of municipal (district, neighbourhood) public facilities and equipment, a municipal library, a health centre or a theatre (Article 40(2)(4)), as well as the rules governing the creation of auxiliary units - villages, neighbourhoods, urban districts (Article 5). In this context, the thesis that municipal statutes (municipal, district, for the capital city of Warsaw) cannot serve as a legal basis for imposing obligations on citizens and their organisations or as a basis for granting them authorisations seems to be unjustified. The municipal budget and the economic programme of this local authority community are types of general local legislation.